The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1126/science.1110787
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Tracing Shows Segregation of Taste Neuronal Circuitries for Bitter and Sweet

Abstract: The recent discovery of mammalian bitter, sweet, and umami taste receptors indicates how the different taste qualities are encoded at the periphery. However, taste representations in the brain remain elusive. We used a genetic approach to visualize the neuronal circuitries of bitter and sweet tastes in mice to gain insight into how taste recognition is accomplished in the brain. By selectively expressing a transsynaptic tracer in either bitter- or sweet and/or umami-responsive taste receptor cells, and by comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 19 publications
(34 reference statements)
2
65
2
Order By: Relevance
“…Although reflexes of acceptance and avoidance might not need the presence of the GC (Grill and Norgren, 1978), our results provided the evidence for functional taste differentiation even at the cortical level, although the territories are not strictly distinct. Our results are in agreement with previous electrophysiological studies (Yamamoto et al, 1985(Yamamoto et al, , 1989 and partially consistent with the genetic tracing study (Sugita and Shiba, 2005) because the labeled neurons might belong to the regions that we found activated by one but not by the other taste modality. However, the presence of overlapping regions does not allow us to state that the two modalities have a segregated cortical representation.…”
Section: Evidences For Segregation (Or Labeled-line)supporting
confidence: 83%
See 3 more Smart Citations
“…Although reflexes of acceptance and avoidance might not need the presence of the GC (Grill and Norgren, 1978), our results provided the evidence for functional taste differentiation even at the cortical level, although the territories are not strictly distinct. Our results are in agreement with previous electrophysiological studies (Yamamoto et al, 1985(Yamamoto et al, , 1989 and partially consistent with the genetic tracing study (Sugita and Shiba, 2005) because the labeled neurons might belong to the regions that we found activated by one but not by the other taste modality. However, the presence of overlapping regions does not allow us to state that the two modalities have a segregated cortical representation.…”
Section: Evidences For Segregation (Or Labeled-line)supporting
confidence: 83%
“…Anatomical and genetic tracing studies also provided evidence of segregated pathways for taste processing from the periphery to the brain in both insects and rodents (Wang et al, 2004;Sugita and Shiba, 2005), confirming that basic organizing principles of sensory processing are conserved among different species. In Drosophila, axon labeling experiments showed that projections from peripheral taste neurons to the brain are segregated by organ and therefore by position of the taste stimulus.…”
Section: Evidences For Segregation (Or Labeled-line)mentioning
confidence: 84%
See 2 more Smart Citations
“…How taste qualities map to these areas is not understood, but a recent study suggests that intermediate brain locations do maintain quality-dependent geography. For instance, most sweet-activated neurons map to the rostral fields of these regions [15].…”
Section: Taste Biologymentioning
confidence: 99%